PENERAPAN MEDIA POP-UP BOOK DIGITAL TERHADAP HASIL BELAJAR SISWA KELAS 5 SD NEGERI CENTRE MAWANG KABUPATEN GOWA - Nurlina; Nurfadilah; Rizqah Magfirah (STKIP Subang, 2025)
This study aims to examine the effect of digital pop-up book media on the learningoutcomes of fourth-grade students at SD Negeri Centre Mawang. A pre-experimental method with a one-group pretest-posttest design was used, involving34 students selected through purposive sampling. The instruments includedmultiple-choice tests and observation sheets. Results showed that the averagepretest score of 58.57 (low category) increased to 90.04 (high category) afterusing the media. Learning mastery improved from 70.6% to 100%, with anormalized gain score of 0.58 indicating a moderate improvement. These findingssuggest that digital pop-up book media effectively enhances student learningoutcomes.